Computational Analysis of Active Phytochemicals Came from GC-MS Chromatogram of Rhynchanthus longiflorus Hook.f. against Thymidine Phosphorylase Enzyme - Anukanon, Shisanupong; Teerapatarakarn, Narudol; Rujjanawate, Chaiyong (Greater Mekong Subregion Medical Journal, 2022)
Background: A previous study reported fifteen identified compounds that were obtained from an essential oil extract from Rhynchanthus longiflorus Hook.f., carried out by using the GC-MS technique, which revealed possible potential candidates for further drug development in cancer chemotherapy. Objective: This study aimed to determine and predict the most effective compound obtained from the GC-MS chromatogram of the essential oil extract from Rhynchanthus longiflorus Hook.f., active against the human thymidine phosphorylase enzyme, again carried out using computational analysis. Materials and methods: All compounds identified by GC-MS analysis were threedimensionally optimized and docked with a well-prepared crystal structure of the human thymidine phosphorylase enzyme. Additionally, the in silico pharmacokinetic properties, bioactive activities, and toxicity profiles prediction were determined. Results: Amongst these identified compounds, beta-eudesmol showed the highest binding affinity against thymidine phosphorylase, with a binding energy of -7.44 kcal/mol, showing better values than that of the reference compound (5-iodouracil). The pharmacokinetic properties, bioactive activities, and toxicity profiles of all compounds met the acceptance criteria. Conclusion: This study suggests that an active phytochemical, revealed by the GC-MS chromatogram, may be a most promising candidate drug, acting on the thymidine phosphorylase enzyme, and so should be studied further.